(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This work includes a theoretical study to the effect of different diffusion lengths of electron on the parameters of the single crystal silicon solar cell. Different values of diffusion length of electron are used and by using electronic calculator programme in visual basic language. The results show increasing the parameters of single crystal silicon solar cell with increasing the diffusion length of electron and consequently calculating the theoretical efficiency of the cell, which varied between (13.352 - 30.076) %. The relationship between values of the diffusion length of electron and the input parameters in calculating the cell efficiency has been drawing and then drawing the relationship between these diffusion lengths and the theoretical efficiency of this cell as well as noticing effect of other parameters on that efficiency and important notes and conclusions is achieved which can be summarized in two features: Firstly: Improving the diffusion lengths in both the top surface and the back surface would reduce losses due to bulk and surface recombination velocities at the front and back surface and bring measured photocurrents closer to the idealized values. Secondly: Using a base layer of a thickness smaller than the minority carrier diffusion length, which improve the collection efficiency of the solar cell.